ANALYSIS OF THE CONDITION AND AREA OF CORAL REEF COVER IN THE WATERS OF PANDAN ISLAND, WEST SUMATRA PROVINCE - Clara, Dina Harven; Thamrin, Thamrin; Amin, Bintal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This research was carried out in January 2024 in the Pandan Island Conservation Area, Padang City, West Sumatra Province. The aim was to determine the condition and the extent of coral reef cover in this area. The method used in this research is a survey method with quantitative analysis using coral reef observation data. Data was collected at three stations using the UPT (Underwater Photo Transect) method, namely by diving using Scuba diving equipment and taking underwater photos using a digital camera. The percentage of coral reef cover at the three stations includes Station I (Pandan Island to the south), which has a coral cover of 67.60% categorized as good, and Station II (Pandan Island to the east), which has a cover of 69.07%, which is classified as good. Station III (Pandan Island to the north) has a cover of 63.04%, categorized as good. The types of growth of living coral reefs (life form) found at Station I are dominated by Coral Foliose (CF) at 44.13%, at Station II, it is dominated by Coral Foliose (CF) at 38.13%, and Coral Encrusting (CE) amounting to 14.73%. In comparison, Station III was dominated by Coral Encrusting (CE), amounting to 20.86%, and Coral Massive (CM), amounting to 15.90%. Based on the image classification results, it can be concluded that the area of ​​living coral reefs in the research area is 14.65 ha.